Bioaccumulation of butyltins and liver damage in the demersal fish Cathorops spixii (Siluriformes, Ariidae) - Santos, Dayana Moscardi dos [UNESP]; Santos, Gustavo Souza; Cestari, Marta Margarete; Oliveira Ribeiro, Ciro Alberto de; Silva de Assis, Helena Cristina; Yamamoto, Flavia; Guiloski, Izonete Cristina; Rodrigues de Marchi, Mary Rosa [UNESP]; Montone, Rosalinda Carmela (Springer, 2014)
The toxicity of butyltin compounds (BTs), mainly tributyltin (TBT), has been reported in different organisms. However, such an analysis in fish after field exposure with reference to the related biomarkers has not been commonly observed in the literature. This study presents the uptake of BTs in the liver of a neotropical marine catfish Cathorops spixii in Paranagua Bay, an important estuarine system located in southern Brazil. Two different areas, close to and distant from the harbor, were used for chemical analysis evaluation of hepatotoxicity through genetic, enzymatic, and histopathological biomarkers. The presence of polycyclic aromatic hydrocarbons in bile was also considered as a biomarker. The results showed a significant relationship between TBT levels and the inhibition of biotransformation enzymes and high occurrence of melanomacrophages in fish collected close to the harbor site. These effects were linked to the absence of TBT metabolites in the liver. In the second site, the presence of DBT was associated with an increase in EROD and GST activity. The larger amount of DNA damage as well as the highest oxidative stress was noted in fish from the less TBT-polluted area, where DBT and bile PAHs occurred. These findings showed different impact levels due to or increased by the chronic exposure of biota to BTs.
Keywords: Butyltin; Estuary; Biomarker; Pollution; Liver; Cathorops spixii